MBS model for control and optimization of a hydrofoil boat. Issue 1 (25th January 2021) - Graf, Matthias
Abstract: The most efficient hull concept for racing boats is a hull completely lifted out of the water by a configuration of hydrodynamic foils. Due to its similarity to an inverted pendulum, the system is intrinsically unstable and requires control mechanisms. This paper describes a typical configuration of a hull and the hydrofoils and the corresponding MBS model. The MBS‐model allows studying parameters for control and hydrofoil positions and is coupled with a global optimizer to choose the most beneficial set of parameters.